2022
DOI: 10.3389/feduc.2022.856237
|View full text |Cite
|
Sign up to set email alerts
|

Transformation toward sustainability in Finnish teacher education policy: Promises and shortcomings

Abstract: While the state of the world is becoming ever more unsustainable, transformation and transformative learning have become increasingly relevant and raised attention in various sustainability education discourses. This is obvious in both policy and research. As teacher educators, we have studied how this sustainability and transformative education trend is visible in education policy. We have first read international policy and research on sustainability education and transformation. In a more thorough study, ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Sustainability has to be a fundamental part of the educational strategy (LOMLOE, 2020;Wolff et al, 2022). The sustainability plan must emanate from the school to create commitment, credibility and clarity in a transverse way throughout the entire educational community.…”
Section: Discussionmentioning
confidence: 99%
“…Sustainability has to be a fundamental part of the educational strategy (LOMLOE, 2020;Wolff et al, 2022). The sustainability plan must emanate from the school to create commitment, credibility and clarity in a transverse way throughout the entire educational community.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, education, culture, and cultural heritage are viewed less as responses to the changing demands of the market economy and more so as tools for promoting sustainable development and respecting human rights and the fundamental freedoms of expression, information, and communication, which are, in turn, considered prerequisites for the creation and dissemination of diverse cultural expressions; promoting equal access, openness, and balance to the flow of cultural services, including courses of action to support diverse cultural manifestations, is also becoming increasingly important (Gesche-Koning 2018; Rieckmann 2020; UNESCO-United Nations Educational, Scientific and Cultural Organization 2022;Varela-Losada et al 2022;Wolff et al 2022a). Thus, culture is viewed not only as a trait that a person possesses or has acquired via assimilation or socialization but also as a dynamic and process-oriented approach that promotes involvement in cultural experiences throughout life and forms a value system based on pre-established knowledge and understandings (Valsiner 2014;Valsiner et al 2021).…”
Section: Relationship Between Educational and Cultural Contextsmentioning
confidence: 99%
“…The transformative approach to the learning process is becoming more and more relevant in the Latvian education space. It is necessary to prepare student teachers to not only be the agents of change but also to be able to preserve and transform educational values in society by encouraging them to question the attitudes and values that underpin their worldviews and social processes (Varela-Losada et al 2022;Wolff et al 2022aWolff et al , 2022b. In this regard, Mezirow (2009) thematizes the quality of education and the importance of culture in the transformation of educational values in the following transformative learning dimensions:…”
Section: Educational Values and Their Transformative Aspects In Teach...mentioning
confidence: 99%
“…The development of Finnish society, the Finnish model, has already shown that it is possible to advance from a relatively poor agricultural country to a high-tech country without abandoning the welfare state by applying similar skill sets (Himanen, 2014). Education can be a tool in this transformation and can be transformed as a part of the process, leading to change and sustainability (Wolff et al, 2022). To achieve this, the Finnish Ministry of Education has outlined that teachers' education should anticipate future needs, based on research, continuous and collaborative, promoting leadership competence (Ministry of Education and Culture, 2022).…”
Section: Finnish Ict Education Modelmentioning
confidence: 99%